Advertising appeals and Malaysian culture norms - Raza, Syed Hassan; Abu Bakar, Hassan; Mohamad, Bahtiar (John Benjamins Publishing Company, 2018)
The ongoing development of the strategic communication research in the area of the advertising calls for the development and validation of the measurement instruments that can address the indulgence of the advertising appeals in a specific cultural context.Therefore, the present study examines and validate advertising appeals by considering the norms based on the GLOBE nine cultural dimensions in Malaysian context.The analysis involved data from 10 advertising expert for content validation, followed by 10 advertising expert rating and ranking of the scale of its relevance and clarity to assess the item-level content validation.The results provided to support the impact of cultural norms are substantial for Malaysian advertising, which are identified from content validation procedure.